Borane-Catalyzed Reduction of Pyridines via a Hydroboration/Hydrogenation Cascade - Yang, Zhao-Ying; Luo, Heng; Zhang, Ming; Wang, Xiao-Chen (ACS catalysis, 2021)
We have developed a method for a B(C6F5)3-catalyzed hydroboration/hydrogenation cascade reduction of pyridines. The method was particularly effective for 2,3-disubstituted pyridines, which generated piperidines in high yields with high cis selectivity. Mechanistic studies indicated that the pyridine substrates and the piperidine products sequentially acted as bases in cooperation with B(C6F5)3 to split H2. The broad functional group tolerance of the method allowed its use for the synthesis of some biologically active molecules.